PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN MODEL MAKE A MATCH KELAS IV - Sulastri, Sulastri; Sugiyono, Sugiyono; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThe study aims to improve student learning outcomes through the use of Make a match models. The method used in this study is a descriptive method in the form of Classroom Action Research, which is collaborative. Data collection techniques used are direct observation and measurement techniques with the subject of the teacher / researcher and fourth grade students totaling 20 students. The results of this study are: 1) The ability of teachers to plan learning can be said to be good because it has experienced a fairly good increase in each cycle. Cycle I starts with a value of 2.87 with a pretty good category, Cycle II has an increase of 0.54 so the value becomes 3.41 which is in the good category. Whereas in Cycle III also experienced an increase of 0.32 so that the value became 3.73 and entered in a very good category. 2) The ability of teachers to carry out learning cycle I with a value of 2.71 with enough categories, cycle II has an increase of 0.57 value to 3.28 which is in the good category. Whereas Cycle III has increased by 0.33 so the value becomes 3.61 in a good category. 3) Student learning outcomes increase in each cycle. Cycle I percentage of student learning outcomes only 57.50 increased by 11 in the second cycle to 68.50 and in the third cycle increased by 6.40 to 74.90 included in the excellent category. Â Keywords: Learning Outcomes, Models Make a match, Citizenship Education.